An Electron‐Accepting aza‐BODIPY‐Based Donor–Acceptor–Donor Architecture for Bright NIR Emission. Issue 16 (19th February 2021) - Kage, Yuto; Kang, Seongsoo; Mori, Shigeki; Mamada, Masashi; Adachi, Chihaya; Kim, Dongho; Furuta, Hiroyuki; Shimizu, Soji
Abstract: A bright near‐infrared (NIR) fluorescent molecule was developed based on the donor–acceptor–donor (D–A–D) approach using an aza‐BODIPY analog called pyrrolopyrrole aza‐BODIPY (PPAB) as an electron‐accepting chromophore. Directly introducing electron‐donating triphenylamine (TPA) to develop a D–A–D structure caused redshifts of absorption and emission of PPAB into the NIR region with an enhanced fluorescence brightness of up to 5.2×10 4  m −1  cm −1, whereas inserting a phenylene linker between the TPA donor and the PPAB acceptor induced solvatochromic behavior in emission. Transient absorption spectra and theoretical calculations revealed the presence of a highly emissive hybridized locally excited and charge‐transfer state in the former case and the contribution of the dark charge‐separated state to the excited state in the latter case. The bright D–A–D PPAB as a novel emitter resulted in a NIR electroluminescence with a high external quantum efficiency of 3.7 % and a low amplified spontaneous emission threshold of ca. 80 μJ cm −2, indicating the high potential for NIR optoelectronic applications. Abstract : Shine, little molecule, shine : A molecule that is bright near‐infrared (NIR) fluorescent owing to a highly emissive hybridized locally excited and charge‐transfer state was developed based on a donor–acceptor–donor (D–A–D) structure comprising a pyrrolopyrrole aza‐BODIPY analog (PPAB) as an acceptor. Its high external quantum efficiency of 3.7 % in electroluminescence studies and low amplified spontaneous emission threshold of circa 80 μJ cm −2 indicate the high potential for NIR optoelectronic applications.